From the paradigm of responsibility for sustainability to the EU law on corporate social responsibility - MacGregor Pelikánová, Radka (<center>Conference Proceedings Determinants Of Regional Development</center>, 2022)
Sustainability has roots going back thousands of years and its evolution goes from the ethical dimension and collective responsibility to international and even national law dimensions and individual responsibility. The EU and EU law have consistently endorsed sustainability and recently they have moved to the issuance of a set of new provisions deserving a developed analysis and critical exploration facilitating their deeper understanding. The need for such an exploration is magnified by recent crises, such as the Covid-19 pandemic and the war in Ukraine, which have multispectral consequences. Since the evolution of sustainability projected into the individual responsibility of business CSR is pretty organic, the appreciation of the new stage of CSR and the teleological interpretation of its framework demands (i) a presentation of theoretical premises represented by the summary of the evolution of the conceptual understanding of responsibility for sustainability along with (ii) the identification of data and method. Based on that, there is presented (iii) a practical overview of EU milestones in the CSR evolution with an implied shift from the collective accountability over individual liability to corporate responsibility. This allows (iv) for selecting the three most relevant instruments of EU policy and law about the sustainability and individual responsibility for it and juxtaposing their teleological interpretation with comparative evolutionary notes and content analysis employing both quantitative aspects (key word counts and frequency or concentration) and qualitative aspects (Delphi assessment and LIWC). Such an exploration, interconnected via Meta-Analysis offers the potential for (v) pioneering conclusions about the modern paradigm of social responsibility, including the revelation of EU law preferences regarding CSR.